Pengaruh Kemampuan Usaha dan Tingkat Pendidikan terhadap Keberhasilan Usaha (pada UMKM Makanan di Magelang) - Bondan Prakoso; Nia Kurniati Bachtiar (Prosiding University Research Colloquium, 2022)
This study aims to examine and analyze the effect of business ability and level of education on business success. The sample in this study was 100 respondents with purposive sampling method. This study uses quantitative methods with descriptive test analysis, validity and reliability tests, multiple linear regression analysis and hypothesis testing with the help of SPSS version 22 program. The results of this study state that Business Ability has a positive and significant influence on Business Success, Education Level has no influence on Business Success, and Business Ability and Education Level together have a positive and significant effect on Business Success.